Exploring Students’ Use of a Mobile Application to Support Their Self-Regulated Learning Processes - Baars, Martine; Khare, Sanyogita; Ridderstap, Léonie (Frontiers in Psychology, 2022)
Being able to self-regulate one’s learning is essential for academic success but is also very difficult for students. Especially first year students can be overwhelmed with the high study load and autonomy in higher education. To face this challenge, students’ monitoring and self-regulated learning processes are crucial. Yet, often students are not aware of effective self-regulated learning strategies or how to use them. In this study, the use of a mobile application with gamification elements (i.e., Ace Your Self-Study App) to support first-year university students’ self-regulated learning processes was investigated. In Study 1a, the Ace your self-study app was implemented in a first-year psychology course and students’ self-regulated learning skills, motivation, self-efficacy, app use and satisfaction, and performance were measured. The results showed a significant increase in autonomous motivation, controlled motivation, and metacognitive self-regulation skills (MSR-R) across the five-week course. Moreover, students who used the mobile application with gamified elements showed higher autonomous motivation. Nevertheless, most students used the app only for a limited number of self-study sessions. In Study 1b, students' self-study experiences were captured using focus group interviews to shed some more light on why students did or did not use the app. The results show that if students feel they do not need support for their self-regulated learning processes during self-study, they are less inclined to use the app. Specifically, regarding using study strategies, it was found that only if students' strategies do not work well in their perception, they feel they the need to change their way of studying and choose another strategy. These results are discussed in the context of theory on self-regulated learning and how to support it.